Case Report: Diagnosis and management of primary ovarian squamous-cell carcinoma: a report of two cases and systematic review of the literature - Guo, Feifei; Huang, Bingna; Hua, Yue; Zheng, Kang; Chen, Jing; Chen, Ling; Jing, Xiujuan; Li, Rong; Zhou, Huaijun (Frontiers in Oncology, 2026)
ObjectiveTo present two cases of primary ovarian squamous-cell carcinoma (POSCC) and describe a comprehensive review and analysis of the published related literature.MethodsWe reviewed the medical records of two patients with POSCC who underwent optimal debulking surgery followed by systemic chemotherapy at Nanjing Drum Tower Hospital. We also reviewed published case reports and case series describing POSCC, focusing on histogenesis, diagnostic approaches, current therapeutic modalities, and prognosis associated with this condition.ResultsThe median age at diagnosis of patients with POSCC was 53.4 years. Few patients were diagnosed at an early stage (stage I, 19.71%), and tumor stage had a significant prognostic effect (p = 0.0081). However, the difference in survival between advanced stages (stage III and stage IV) was small and not statistically significant. Most patients underwent hysterectomy and bilateral salpingo-oophorectomy, and omentectomy and lymphadenectomy improved survival outcomes in patients with advanced-stage disease.ConclusionPrimary ovarian squamous-cell carcinoma is a rare and challenging type of ovarian cancer, and its prognosis remains extremely poor. Aggressive multimodal treatment may include surgery, systemic chemotherapy, and targeted therapies.